Diagnosis of prenantal holoprosencephalic agnatia complex (2011)
The complex agnatia holoprosencephaly (CAH) is characterized by absence or severe hypoplasia of the mandible, abnormal position of the ears, microstomia and holoprosencephaly. A case of mother son aged 34, gravida 3, part 2, with multiplanar three-dimensional ultrasound diagnosis of holoprosencephaly and anatomical detail otocefalia, so diagnosis of CAH was made. A review of the literature and discuss the differential diagnosis.